Difusi Inovasi dalam Film “Toilet” - Fransiska Fransiska (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Sanitation is a polemic faced by developing countries. There are various reasons why sanitation is still underdeveloped in some areas such as poverty, culture, customs and others. Inability to sanitation can unknowingly result in losses for the community, losses experienced such as the emergence of diseases such as skin diseases, dirty environments and well water pollution. The purpose of this study is to illustrate that it is not easy to adopt a habit in society that is translated into an Indian film entitled